Dysocjacja jako hard case w systemie prawa - Helios, Joanna; Jedlecka, Wioletta (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The monograph is regarding comprehending the dissociation as the so-called hard case in the system of law, in particular of criminal law and educational. At the work they assumed that a dissociation was defense mechanism which relies on the fact that the individual is separating the emotional plot, emotion, emotion associated with some idea, object or compound. It is about a siltation from itself senses of responsibility too committed some, respect arousing fear and lowering for oneself, act. They emphasized that it was possible in a way to bring understanding the dissociation about for the process of partial or total correct loss of integration between memories from the past, feeling the identity, sensory impressions and the inspection of moves of the body. This recognized dissociation generates a series of problems in the legal system. The monograph focuses on criminal law (insanity, sanity limited, other disturbances of mental activity) and education law (the right to education / compulsory schooling, home education, the rights of the child). In the legal system problems due to a lack of knowledge of the concept of dissociation, including a small expertise.
Keywords: dissociation; trauma; hard case; system of law; criminal law; insanity; fault; protection standards of children's rights; education law